Liver Involvement is Associated with Higher Risk of Rapidly Progressive Interstitial Lung Disease and Mortality in Anti-Melanoma Differentiation-Associated Gene 5 Antibody- Positive Dermatomyositis - Yang X; Cui X; Yang X; Ren B; Cheng X; Zhao X; Liu S; Tian T; Zhao H; Qu L; Li X (Dove Medical Press, 2024)
Xin Yang,1 Xiaoguang Cui,1 Xiao Yang,2 Bincheng Ren,1 Xiaojing Cheng,1 Xinrui Zhao,1 Shanshan Liu,1 Tian Tian,1 Hui Zhao,1 Li Qu,1 Xueyi Li1 1Department of Rheumatology, Xi'an Jiaotong University Second Affiliated Hospital, Xi'an, People's Republic of China; 2Scientific Research Center and Precision Medical Institute, Xi'an Jiaotong University Second Affiliated Hospital, Xi'an, People's Republic of ChinaCorrespondence: Xueyi Li, Department of Rheumatology, Xi'an Jiaotong University Second Affiliated Hospital, Xi'an, People's Republic of China, Tel +86 13992891987, Fax +86 02987679832, Email li-xueyi@139.comPurpose: This study aimed to assess liver involvement and investigate its correlation with rapidly progressive interstitial lung disease (RP-ILD) and mortality in anti-melanoma differentiation-associated gene 5 antibody-positive (anti-MDA5 positive) DM patients.Patients and Methods: This retrospective study included 159 patients diagnosed with anti-MDA5 positive DM or anti-synthetase syndrome (ASyS). Clinical features and laboratory findings were compared between patients with anti-MDA5 positive DM and patients with ASyS. In the anti-MDA5 positive DM cohort, clinical features and laboratory findings between patients with liver involvement and without liver involvement were further compared. The effects of liver involvement on the overall survival (OS) and development of RP-ILD were also analyzed using Kaplan-Meier method and Cox regression analysis.Results: Levels of serum aspartate aminotransferase (AST), alanine transaminase (ALT), γ-glutamyl transferase (γGT) and alkaline phosphatase (ALP) were all significantly higher in patients with anti-MDA5 positive DM than those in patients with ASyS. In our cohort of anti-MDA5 positive DM patents, 31 patients (34.4%) were complicated with liver involvement. Survival analysis revealed that serum ferritin > 1030.0 ng/mL (p< 0.001), ALT > 103.0 U/l (p< 0.001), AST > 49.0 U/l (p< 0.001), γGT > 82.0 U/l (p< 0.001), ALP > 133.0 U/l (p< 0.001), lactate dehydrogenase (LDH)> 474.0 U/l (p< 0.001), plasma albumin (ALB) < 35.7 g/l (p< 0.001) and direct bilirubin (DBIL) > 2.80 μmol/l (p=0.002) predicted poor prognosis. The incidence of RP-ILD increased remarkably in patients with liver involvement compared to patients without liver involvement (58.1% vs 22.0%, p=0.001). Multivariate analysis revealed that elevated serum ALT level was an independent risk factor for mortality (HR 6.0, 95% CI 2.3, 16.2, p< 0.001) and RP-ILD (HR 5.9, 95% CI 2.2, 15.9, p< 0.001) in anti-MDA5 positive DM patents.Conclusion: Liver involvement is common in patients with anti-MDA5 positive DM. Elevated serum ALT level was an independent risk factor for RP-ILD and mortality in patients with anti-MDA5 positive DM.Keywords: anti-melanoma differentiation-associated gene 5 antibody, liver involvement, ferritin, macrophage, interstitial lung disease, dermatomyositis